Promoting Mental Health And Wellness In Healthcare Organizations: Strategies For Health Administrators (Journal of Namibian Studies : History Politics Culture, 2022)
Promoting mental health and wellness among healthcare professionals is essential for maintaining quality patient care and organizational effectiveness. Health administrators play a vital role in creating supportive environments conducive to mental well-being. This article explores strategies for health administrators to foster mental health and wellness within healthcare organizations. Key approaches include establishing supportive cultures, prioritizing employee wellness programs, implementing mental health support services, enhancing work environments, and monitoring outcomes. By implementing these strategies, administrators can create healthier workplaces where employees thrive, leading to improved patient care and organizational success.